National philosophy as phenomenon of cultural-civilizational development - Lazarevich, Anatoly A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
In the article, the phenomenon of national philosophy is discussed in four aspects. First, in the disciplinary aspect, where it is presented as an organized activity for production of humanitarian knowledge and methodological support of scientifictechnical activity. Second, national philosophy is interpreted through the prism of philosophical culture as a complex of value and cognitive orientations that are transmitted from generation to generation. Third, national philosophy is considered in the aspect of tradition of the study of philosophical thought of people and state on the path to its historical formation. Fourth, national philosophy is characterized in the aspects of philosophical grounds of the national idea, ideology of state and cultural development. It is underlined that national philosophy plays an important role in ensuring cultural diversity,serves as a guarantee of continuity of spiritual traditions of society. In the modern world, it serves as a source of heuristic tools for the search of effective local responses to global problems of social-natural development.
Keywords: nation; state; national philosophy; national culture; philosophical culture